The Prior Consultation of Indigenous Peoples in Latin America Inside the Implementation Gap - Wright, Claire; Tomaselli, Alexandra (Taylor & Francis, 2019)
This book delves into the reasons behind and the consequences of the implementation gap regarding the right to prior consultation and the Free, Prior and Informed Consent (FPIC) of Indigenous Peoples in Latin America. In recent years, the economic and political projects of Latin American States have become increasingly dependent on the extractive industries. This has resulted in conflicts when governments and international firms have made considerable investments in those lands that have been traditionally inhabited and used by Indigenous Peoples, who seek to defend their rights against exploitative practices. After decades of intense mobilisation, important gains have been made at international level regarding the opportunity for Indigenous Peoples to have a say on these matters. Notwithstanding this, the right to prior consultation and the FPIC of Indigenous Peoples on the ground are far from being fully applied and guaranteed. And, even when prior consultation processes are carried out, the outcomes remain uncertain. This volume rigorously investigates the causes of this implementation gap and its consequences for the protection of Indigenous Peoples' rights, lands, identities and ways of life in the Latin American region.